2021
DOI: 10.1002/adem.202101110
|View full text |Cite
|
Sign up to set email alerts
|

Microextrusion Foaming of Polyetheretherketone Fiber: Mechanical and Thermal Insulation Properties

Abstract: Porous polyetheretherketone (PEEK) materials, especially those with controllability and excellent mechanical properties, have always been the development hotspots in the fields of thermal insulation and medical bone implants. However, the traditional sulfonation process of porous PEEK materials has the problems of applying abundant high‐concentration solvents, high production costs, low resource utilization, and environmental pollution. Herein, a microextrusion foaming process with using CO2 as a blowing agent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…The combination of high-pressure mixing and a sudden pressure drop can readily lead to the coalescence, rupture, and annihilation of internal cells within the foam melt. This phenomenon results in an uneven cell size and distribution, a sparse cell structure, and other varied structural morphologies in the final product [ 75 , 90 , 91 , 92 , 93 , 94 , 95 ]. To improve the cell morphology in continuous extrusion foaming, it is necessary to control complex parameters to enhance cell nucleation with nanoparticles and to restrict cell coalescence by increasing the melt strength of the polymer [ 93 , 96 , 97 ].…”
Section: Mefmentioning
confidence: 99%
See 2 more Smart Citations
“…The combination of high-pressure mixing and a sudden pressure drop can readily lead to the coalescence, rupture, and annihilation of internal cells within the foam melt. This phenomenon results in an uneven cell size and distribution, a sparse cell structure, and other varied structural morphologies in the final product [ 75 , 90 , 91 , 92 , 93 , 94 , 95 ]. To improve the cell morphology in continuous extrusion foaming, it is necessary to control complex parameters to enhance cell nucleation with nanoparticles and to restrict cell coalescence by increasing the melt strength of the polymer [ 93 , 96 , 97 ].…”
Section: Mefmentioning
confidence: 99%
“…Based on our preceding discussion, the fabrication of porous fibers using the MEF method is not only theoretically feasible but also holds great promise for practical applications. Li et al [ 90 ] first used the MEF method to prepare porous polyetheretherketone (PEEK) fibers and achieved success. They utilized PEEK’s low gas diffusion rate and high T g to manufacture porous PEEK fibers with internal micropores and rough surface structures, and they studied the effects of different process parameters on the pore morphology of porous PEEK fibers.…”
Section: Mef For Porous Fibersmentioning
confidence: 99%
See 1 more Smart Citation
“…It was found that foaming of high crystallinity PEEK yielded small cells of about 5–10 um, which are generally considered too small for bone tissue engineering. Li et al 20 used the microcellular extrusion foaming method with CO2 to fabricate porous PEEK filaments. High toughness and excellent thermal insulation properties were achieved; however, the filaments were foamed during the extrusion process, with limited control on the pore size.…”
Section: Introductionmentioning
confidence: 99%